Impaired Cognition – A Menace to Aging - Sujitha P; Swetha NB (National Journal of Community Medicine, 2023)
Cognition is defined as mental process of acquiring knowledge and understanding through thought, experience and senses. It is an age-related degenerative condition, as the age advances, individuals experience deteriorative changes in their cognitive abilities. It is estimated that nearly four fifth of the elderly above 60 years of age will be living in developing countries like Africa, Asia by 2050, thereby placing the developing countries to face threat of cognitive impairment among elderly when compared to developed countries. The result of striking increase in ag-ing population of India, it is expected to have a substantial increase in elderly suffering from cognitive impair-ment. This review involves discussing the various causes, pathophysiology, modifiable and non-modifiable risk factors associated with this increasing cognitive deterioration in elderly people, diagnostic criteria, and preven-tive methods. This review will help in better understanding of the cognitive impairment in elderly people. Better understanding of the disease helps in better treatment modalities.